An analysis of technical efficiency on pepper farm in Sarawak - Radam, Alias; Ismail, Mohd Mansor (Universiti Putra Malaysia, 1994)
The principal objective of this paper is to understand the extent to which the pepper farmers ill Sarawak exploit their resources ill the production of pepper and 10 estimate the input-alii put relationship of any particular activity ill pepper farming in Sarawak. Cross-sectional data from 163 pepper farmers were used for the study. The frontier production function estimated by the Corrected Ordinary Least Squares (COLS) technique was employed in the analysis. The result indicated that the farmers achieved relatively low levels of physical efficiency ill growing pepper. It is apparent that the efficiency level of resource lise ill pepper production ill Sarawak could be improved